Why Are All the White Kids Sitting Together in the Cafeteria?: Toward Challenging Constructions of a Persecuted White Collective - Uma Mazyck Jayakumar; Annie S. Adamian; Sara E. Grummert; Cameron T. Schmidt-Temple; Andrew T. Arroyo (MDPI AG, 2021)
In the context of ongoing antagonism on college campuses, attacks on Critical Race Theory, and widespread backlash against racial justice initiatives, this paper underscores the growing need to recognize co-optation and other counterinsurgent strategies used against racial justice to make room for transformative scholarship. By presenting qualitative interviews from 15 white HBCU students, we illustrate how diversity research, advocacy, and organizing previously used to advocate for racial justice has instead constructed distorted understandings of race and racism and has been used to expand ideologies of whiteness. The findings show what CRT scholars have cautioned about for decades-when left uninterrupted, ahistorical approaches to racial diversity programming and research may lend to the co-optation of justice-focused diversity language and the appropriation of BIPOC strategies of resistance. This not only inhibits and detracts from racial justice work, but can function to expand white supremacy. We relate these narratives to an emerging racial backlash whereby white people attempt to distort understandings of structural racism to claim a "persecuted" status-a delusion that we argue warrants a new ideological frame. We posit this work lays the foundation for advancing equity in one of the most counterinsurgent eras in higher education (Matias & Newlove, 2017).